Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Material Requirement Planning pada PT XYZ - Nabila Kurnia Ramadhani (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
This research focuses on proper raw material inventory control and minimum cost control at PT XYZ. From observation data in 2023, it is known that there is an overstock of copper slag material of 50,160 tonnes, and there is a stockout of gypsum material of 44,403 tonnes and clay of 73,574 tonnes. This research aims to determine appropriate raw material inventory control to identify problems and provide alternative suggestions. The factor that causes stockouts and overstocks in storage is the non-optimal supply of raw materials, such as gypsum material, from February to April there was no material ordering activity. This research uses the Material Requirement Planning method with Lot For Lot and Fixed Order Quantity lotting techniques. Based on the results of the analysis, it was concluded that the gypsum and copper slag materials using the LFL lotting technique produced minimum costs compared to using the FOQ lotting technique, with a difference in the total cost of the gypsum material of IDR. 402,329,503.8 and the difference in the total cost of copper slag material is Rp. 779.1363.022.5. In contrast to clay materials, the FOQ lotting technique produces minimum costs compared to using the LFL lotting technique with a difference in total clay material costs of IDR. 384,902,040. The right solution for controlling raw material inventory at PT XYZ is to use the MRP data processing method and the Lot For Lot lotting technique with a large percentage of gypsum of 1.48%, and copper slag of 8.17%.